A simple solution for detecting mismatching palindromes in a string - Grossi, Roberto (1991)
Abstract: "In this paper we address the problem of detecting all the palindromes with k mismatches contained in arbitrary positions of a given string of length n. We first propose a simple approach that requires O(nk) time. Then, imposing a lower bound on the size of the mismatching palindromes, we show how to attain an expected O(n) time solution by means of matching statistics [CL90, Cr87, GG88]."
Keywords: Palindromes; Pattern perception